Study of Antibiotic Resistance to Pseudomonas aeruginosa that Iisolate from Burns and Ggeneral Surgery from Al-Yarmouk Teaching Hospital - Al-Bidhani, Faraj Hato-Joni (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
Pseudomonas aeruginosa is common gram negative rod – shaped bacterium, a species of considerable medical importance, P. aeruginosa is prototypical "multi drug resistant (MDR) Pathogen" that is recognised for its ubiquity, its intrinsically advanced antibiotic resistance mechanisms, and its associatation with serious illnesses – especially nosocomial infection such as ventilator – associated pneumonia and various sepsis syndromes. This study was conducted from March 2014 to July 2014, the patients were males and females. Total samples of 613 patients, selected from burns wards and general surgery wards, the samples were sending to teaching laboratories from the same hospital. The present study showed that the prevalence of sensitivity revealed that amikacin had the highest sensitivity (89,6%), followed by cefotaxime (66.2%), the optimal aminoglycosides in combination therapy with B-lactams was amikacin, followed by tobramycin and gentamycin, highest sensitivity rate showed that (95.2%) was found in the combination of amikacin with imipenem and piperacillin, (71.4%) were amikacin combination with cefotaxime ,(85.7%) were gentamycin with piperacillin , (71.4%) were gentamycin with cefotaxime, (95.2%) were tobramycin with piperacillin,(76.2%)were tobramycin with carbenicillin, resistance of bacterials associated with reduced aminoglycoside accumulation the current study indicated that pseudomonas aeruginosa was the most prevalent in burns and general surgery infection, these infections generally require treatment with a combination of antimicrobials inoder to achieve a greater baetericidal effect and reduce the levels of resistance .